Diet and Headache: Part 2. Issue 9 (October 2016) - Martin, Vincent T.; Vij, Brinder
Abstract : Background: Comprehensive diets do not require the exclusion of a specific provocative food or ingredient, but regulate the quantities of core components of foods such as vitamins, ions, proteins, carbohydrates, and fats. Objectives: To review the evidence supporting the use of comprehensive diets in the prevention of migraine and other headache disorders and to discuss the mechanisms through which food, and ingredients within foods and beverages might trigger attacks of headache Methods: This represents Part 2 of a narrative review of the role of diet in the prevention of migraine and other headache disorders. A PubMed search was performed with the following search terms: "folate, " "vitamin D, " "low fat diet, " "omega‐3 and omega‐6 fatty acid diet, " "ketogenic diet, " "Atkins diet, " and "sodium." Each of these search terms was then crossreferenced with "headache" and "migraine" to identify relevant studies. Only studies that were written in English were included in this review. Results: Low fat and high omega‐3/low omega‐6 fatty diets decrease the frequency of attacks of migraine and/or other headache disorders as demonstrated in two separate randomized controlled trials. A ketogenic diet was more effective than a standard diet in reducing the frequency of migraine in a single nonrandomized clinical study. An observation study found that dietary consumption of folate was inversely associated with the frequency of migraine attacks in persons with migraine with aura that have the C variant of the methylene tetrahydrofolate reductase gene. The mechanisms though which diets may precipitate headache include their effects on neuropeptides, neuro‐receptors and ion channels, inflammation, sympathetic nervous system, release of nitric oxide, vasodilation, and cerebral glucose metabolism. Conclusions: Evidence exists to support the use of comprehensive diets in the prevention of migraine and other headache disorders. However, the results of these studies should be considered preliminary until replicated in larger randomized controlled clinical trials.